Gang Involvement, Mental Health Difficulties and Exposure to Violence in 11-16-Year-Old School Students - Naldrett, Georgia A.; Wood, Jane L (Adolescent Psychiatry, 2020)
Background and Goals: The current study investigated the relationship between gang involvement and multiple mental health difficulties; anxiety, depression, paranoia, victim trauma and perpetrator trauma. Additionally, it examined the mediating influence of an individual’s exposure to violence within this relationship. Method: One hundred adolescents aged 11-16 years old completed two questionnaires and an interview which investigated their friendship groups, exposure to violence and mental well-being. Eighteen participants were identified as current or ex-gang members and the other eighty-two were classified as the nongang comparison group. Results: Findings show that gang members displayed more symptoms of depression and perpetrator trauma compared to non-gang members. The relationship between gang involvement and these mental health difficulties was mediated by exposure to violence. Conclusion: Discussion focuses on the need for researchers, practitioners and policymakers to acknowledge the relationship between gang involvement and mental health difficulties and implement additional strategies to support young people currently or previously involved in gangs.
Keywords: anxiety